(untitled) (Altre Modernità, 2013)
The recent history of Argentina seems to be pitted with sudden and premature deaths, projecting into myth that ’special’ life in which mystery – the nebulous nature of origins and / or death, the tormented odyssey of the corpse – often accompanies the personage, enabling the process of mystifying: the funeral becomes a crucial point in the ’unveiling’ of a destiny - «muor giovane colui ch’al cielo è caro» - but also a tragic event in itself, the end of an era and a dream ,if not of the world. Carlos Gardel and Eva Duarte are such archetypes. Focusing in particular on Evita, the literature has emphasized the post-mortem as a place of confrontation between Good and Evil, but also between History and Myth: the funeral that provokes apocalyptic scenes, the embalming of a body as a model of nationhood, the theft of the corpse as erasure of history. Several Argentine writers - Tizziani, Posse, Dujovne Ortiz, Walsh, Martínez, Borges, Bellone, Viñas, Perlongher, Szichman, Copi - are confronted with the apocalyptic dimension of death and the post-mortem of Evita.